Adubação nitrogenada associada à inoculação com Rhizobium tropici na cultura do feijoeiro - Spineli, Mariana Caroline (2015)
The objective of this research was to evaluate the association between inoculation and application of nitrogen fertilizers in planting and cover the bean (Phaseolus vulgaris L.). The experiment was conducted in the field in Vegetable Crops experimental sector of the Faculty of Agronomy of the University José do Rosário Vellano - Unifenas, Alfenas - MG. The experimental design was randomized blocks, with eight treatments and three repetitions, being a control treatment without addition of inoculant and fertilizer, the other treatments were made up of N at planting, nitrogen in N at planting and coverage, inoculation and N in planting, inoculation and nitrogen in inoculation and N at planting and coverage, and only one treatment using only inoculation. We used the species Rhizobium inoculant tropici strain CIAT 899T, which was cultured in 79, containing bromothymol blue and pH 6.8, until the appearance of isolated colonies. These were transferred to liquid medium 79 for three days under stirring at 28 ° C until log phase growth containing approximately 108 cells ml-1. Sixty milliliters of this bacterial suspension was inoculated in 1400 using seeds cv. Pearl. All treatments received fertilization of 110 kg ha-1 of P2O5 and 50 kg ha-1 K2O at planting, after planting to 38 daysall treatments also received fertilization applied via leaf molybdenum. Nitrogen fertilization corresponded to 40 kg ha-1applied at planting and 60 kg ha-1applied in coverage at 28 days foliar. We evaluated the dry weight parameters of shoot (PSPA), shoot nitrogen content (TNPA), number of nodes (NN) and dry weight of nodules (PSN), nitrate reductase activity (NRA) in the flowering period, and number of pods per plant (NVP), number of seeds per plant (NSP), grain productivity (kg ha-1) and grain yield in bag of 60 kg ha-1. The results were that the inoculation is a practical feasible, and should be used in areas where there is used nitrogen fertilizer. The use of inoculant in association with nitrogen fertilization promoted higher plant growth and production of dry beans.